शिरीषको फुल उपन्यासमा निस्सारता - Khatiwada, Lekharaj (Haimaprabha, 2025)
The present study analyzes Parijat's novel Shirishko Ful on the basis of existentialism, namely futility, and for that, the descriptive method has been mainly adopted. Existentialism holds that the life of all people born in this strange world without a reason and all of them are living aimlessly. This belief of existentialism has been expressed very skillfully in this novel. Suyogbir, Sakambari and Shivraj in the present novel are shown living in futility and meaningless lives. The existentialist thought that as soon as a person makes a decision in life, an anomaly arises and a person is forced to live life not as he has expected which is expressed through Suyogbir, Sakambari and Shivraj in the present novel. On the basis of these three characters and their actions futility, the fundamental measure of existentialism, has been explored in this study.